2013
DOI: 10.5772/56581
|View full text |Cite
|
Sign up to set email alerts
|

The Exact Euclidean Distance Transform: A New Algorithm for Universal Path Planning

Abstract: The Path-Planning problem is a basic issue in mobile robotics, in order to allow the robots to solve more complex tasks, for example, an exploration assignment in which the distance given by the planner is taken as a utility measure. Among the different proposed approaches, algorithms based on an exact cell decomposition of the environment are very popular. In this paper, we present a new algorithm for universal path planning in cell decomposition, using a raster scan method for computing the Exact Euclidean D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…It was also observed that navigation in multiples of 45º is restrictive and requires a greater demand on the processor to perform the computations necessary. This can be improved by applying the Exact Euclidean Distance Transform algorithm [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that navigation in multiples of 45º is restrictive and requires a greater demand on the processor to perform the computations necessary. This can be improved by applying the Exact Euclidean Distance Transform algorithm [17].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the current position of the robot in the global reference, a new matrix is build, containing the distance of each cell to the destination, in order to bypass the obstacles with the respective margin of safety. This matrix is determined according to the Jarvis' distance transform algorithm with a Euclidean scan window [17], as presented in Fig. 9.…”
Section: Planning and Navigationmentioning
confidence: 99%
“…From experimental results, they recommeded Meijster's (Meijster, Roerdink, & Hesselink, ) method with time complexity of O ( N ), where N is the total number of pixels, to be the best option for computing 2D‐EDT. Elizondo‐Leal, Parra‐González, and Ramírez‐Torres () proposed a EDT to solve a mobile robotics path‐planning problem with complexity of O ( m 2 n ) for an m × n image, at the worst conditions. Moreover, DTs have also been widely applied to shortest path planning (Shih & Wu, ), weather analysis and forecasting (Brunet & Sills, ), skeletonization (Arcelli, Baja, & Serino, ), and other problems.…”
Section: Search Methodologymentioning
confidence: 99%
“…Namun, hasil pelacakan yang ditampilkan adalah hasil optical flow. Jarak koordinat hasil pelacakan dihitung dari kedua algoritma tersebut seperti yang ditunjukkan dalam Gambar 3 menggunakan P ersamaan 1, seperti dalam [13]- [15]. Jika jaraknya lebih dari 10 piksel, maka dilakukan update koordinat dengan cara koordinat pelacakan menggunakan optical flow digantikan dengan koordinat pelacakan template matching.…”
Section: Metode Penelitianunclassified